2016
DOI: 10.1016/j.ijpharm.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Efficient approach to enhance drug solubility by particle engineering of bovine serum albumin

Abstract: Please cite this article as: Khoder, Mouhamad, Abdelkader, Hamdy, ElShaer, Amr, Karam, Ayman, Najlah, Mohammad, Alany, Raid G., Efficient approach to enhance drug solubility by particle engineering of bovine serum albumin.International Journal of Pharmaceutics http://dx.doi.org/10. 1016/j.ijpharm.2016.11.019 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…In a recent study, we demonstrated the possible use of BSA as solubility enhancer for indomethacin as ionisable drugs model, where the solubility was improved up to 10 5 times after formulating it in BSA solid dispersion (Khoder et al, 2016). This spectacular solubility enhancement was mainly attributed to the formation of salts bridges between indomethacin carboxylate groups and BSA amino groups.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a recent study, we demonstrated the possible use of BSA as solubility enhancer for indomethacin as ionisable drugs model, where the solubility was improved up to 10 5 times after formulating it in BSA solid dispersion (Khoder et al, 2016). This spectacular solubility enhancement was mainly attributed to the formation of salts bridges between indomethacin carboxylate groups and BSA amino groups.…”
Section: Discussionmentioning
confidence: 96%
“…Unionisable drugs are not expected to form salts with BSA molecules, yet they might bind to albumin molecules and form a reversible drug-albumin binding complex of higher solubility (Ghuman, Zunszain, Petitpas, Bhattacharya, Otagiri andCurry 2005, Urien, Tillement andBarré 2007). Additionally, converting the drug into a molecular and/or amorphous state that is homogeneously dispersed within the hydrophilic matrix provided by BSA might actively contribute in the enhancement of drug solubility and dissolution rate (Graeser et al 2010, Hancock and Zografi 1997, Huang and Dai 2014, Khoder et al, 2016. PRD:BSA solid dispersions were obtained using two different particle engineering technologies; spray-drying and freeze-drying.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common pharmacological approaches to solubilize poorly water-soluble compounds include surfactant addition, cosolvency, and complexation [4,18,19]. We explored the effects of the common surfactants Tween 80, Triton X-100, vitamin E TPGS, and Cremophor EL at concentrations of 0.03125-0.5% v/v in an effort to fully or partially solubilize nifedipine, a water-insoluble compound that is clinically utilized as a tocolytic.…”
Section: Determination Of Surfactant Cosolvent and Complexation Effects In The Organ Bathmentioning
confidence: 99%